Concise total synthesis of acylated phenolic glycosides vitexnegheteroin A and ovatoside D. (2nd May 2018) - Yan, Shiqiang; Ren, Sumei; Ding, Ning; Li, Yingxia
Abstract: Starting from readily available vanillin and α-D-acetobromo glucose, two natural acylated phenolic glycosides vitexnegheteroin A and ovatoside D were synthesized for the first time in 4 steps with overall yields of 54% and 65%, respectively. The key steps involve the directly regioselective O -6 acylation of vanillin β-D-glucopyranoside with acyl chlorides, and simultaneous removal of the allyl protecting groups on the phenolic acid moiety and reduction of the aldehyde in the aglycon moiety by using Pd(PPh)3 -NaBH4 system in one pot. Graphical abstract: Highlights: The first total synthesis of vitexnegheteroin A and ovatoside D. Short reaction steps (only 4 steps). High overall yields (54% and 65% respectively).